Evaluation of local tumor residue after percutaneous radiofrequency ablation therapy for hepatocellular carcinoma - Hamanaka, Jun; Goto, Tohru; Nishigori, Shuhei; Seki, Shihoko; Ida, Tomonori; Morohashi, Taiki; Ohara, Hiroshi; Inamori, Masahiko; Maeda, Shin (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: This study’s purpose was to compare the efficacy of CO2-enhanced ultrasonography (US) with that of Sonazoid-enhanced US and conventional US in detecting local tumor residue after percutaneous radiofrequency (RF) ablation therapy for hepatocellular carcinoma. Materials and Methods: Between February 2009 and March 2010, 141 lesions of 121 hepatocellular carcinoma patients were treated by percutaneous RF ablation, and 22 tumor residues were detected in 22 patients by contrast-enhanced computed tomography. These 22 patients were examined by conventional US, Sonazoid-enhanced US (0.5 mL/body of Sonazoid, intravenous administration), and CO2-enhanced US (10 mL of CO2, hepatic arterial administration). Results: Tumor residue was confirmed by CO2-enhanced US in all the 22 patients (sensitivity: 100%) in 19 of the 22 patients by Sonazoid-enhanced US (sensitivity: 86%; 3 lesions that were not detected by this modality were located deeper than the sonographic depth (p=0.0109)), and in 17 of the 22 patients by conventional US (sensitivity: 77%; 5 lesions that were not detected by this modality were smaller in terms of the sonographic tumor size (p=0.0278)). Conclusion: Although CO2-enhanced US requires angiography, it was superior to both Sonazoid-enhanced US and conventional US for detecting tumor residues, particularly deep-seated ones, after percutaneous RF ablation.